My Reflexivity on Pedagogical Practices of Physics Teachers - Ghimire, Pankaj Sharma (Educative: Jurnal Ilmiah Pendidikan, 2024)
This paper aims to elaborate my reflection on the instructional practices of physics teachers in theory and experimental classes at technical institutions in the Kathmandu district. I employed an ethnographic research design to conduct the research. I selected two technical institutions in the Kathmandu district to conduct the research, two theory classrooms, and two physics laboratories of those institutions for the participant observation process, and conducted open-ended and unstructured interviews with nine students from those institutions. I observed multiple theory and experimental classes for the entire semester period as a complete observer. In addition, I employed social constructivist learning theory to guide the whole research process. The findings from this study indicated that traditional teacher-centric pedagogical practices were prevalent at those technical institutions.